Durability and reliability of polymers and other materials in photovoltaic modules - Yang, Hsinjin Edwin; French, Roger; Bruckman, Laura (PDL handbook series., 2019)
Durability and Reliability of Polymers and Other Materials in Photovoltaic Modules describes the durability and reliability behavior of polymers used in Si-photovoltaic modules and systems, particularly in terms of physical aging and degradation process/mechanisms, characterization methods, accelerated exposure chamber and testing, module level testing, and service life prediction. The book compares polymeric materials to traditional materials used in solar applications, explaining the degradation pathways of the different elements of a photovoltaic module, including encapsulant, front sheet, back sheet, wires and connectors, adhesives, sealants, and more. In addition, users will find sections on the tests needed for the evaluation of polymer degradation and aging, as well as accelerated tests to aid in materials selection. As demand for photovoltaics continues to grow globally, with polymer photovoltaics offering significantly lower production costs compared to earlier approaches, this book will serve as a welcome resource on new avenues.